PENINGKATAN HASIL BELAJAR SISWA KELAS II SDN KRAMAT I KOTA CIREBON PADA MATA PELAJARAN PENDIDIKAN PANCASILA MELALUI PENDEKATAN BERDIFERENSIASI - Nikken Dwi Retno Sari; Musyfiah; Niken Ayu Choirunnisa; Nugraha Permana Putra; Hendi Suhendi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve student learning outcomes in the Pancasila Education subject with the topic "My Attitude of Caring for the Environment" at SDN Kramat 1, Cirebon City. This classroom action research was carried out collaboratively and consisted of two cycles. The activity began with the pre-cycle stage, namely the provision of cognitive tests to measure students' initial abilities in the Pancasila Education subject. The next stage is the implementation of cycle I, which includes: a) Planning, with activities to compile teaching modules, teaching materials, observation sheets, LKPD, and assessments; b) Implementation of actions; c) Observation; and d) Reflection. The purpose of reflection itself is to assess the advantages and disadvantages of learning in cycle I, which are then used as a reference in designing improvements for cycle II. The results of the study showed that in the implementation of cycle I, the average value of student learning outcomes was recorded at 56.77. In cycle II, there was an increase in learning outcomes with an average value reaching 92.6, which was above the Minimum Completion Criteria (KKM). Based on these results, it can be concluded that the cognitive learning outcomes of grade II students of SDN Kramat 1 Kota Cirebon on the material "My Attitude of Caring for the Environment" have increased significantly.